1988
DOI: 10.1159/000132633
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype evolution in the bone marrow of a patient with Fanconi anemia: breakpoints in clonal anomalies of this disease

Abstract: A 21-year-old Fanconi anemia patient developed refractory anemia. Laboratory studies revealed a transitory increased platelet count and a typical del(5q). Bone marrow karyo-typing showed a -6, + der(6)t(1;6)(q12;p25) rearrangement and, two years later, a mosaic-6,-1-der(6), t(1:6)(q12;p25)/-2, +der 2), t(l;2)(q12;q37) constitution. The chromosome mechanism operating in this patient is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 2 publications
0
11
2
Order By: Relevance
“…We have hypothesized that a deficiency in DNA repair in this region could account for the observed fragility. Some indirect evidence supports this working hypothesis: (1) there is a hierarchy in DNA repair, being the non-transcribed regions and the non-transcribed strand of active genes less efficiently repaired (Bohr et al, 1985;Mellon et al, 1986Mellon et al, , 1987Venema et al, 1990;Mullenders et al, 1991); (2) earlier studies demonstrated that highly repetitive heterochromatic alpha DNA from monkey cells was deficient in excision repair of chemical adducts, although damage induction was not (Zolan et al, 1982;Smith, 1987); (3) 1q12 is frequently broken in cells from Fanconi anaemia patients (Huret et al, 1988), an autosomal recessive genetic syndrome characterized by predisposition to leukemia and solid tumors, elevated spontaneous chromosome breakage, and inability to remove cross-linking lesions from DNA (reviewed by Strathdee et al, 1992); and (4) studies performed with Chinese hamster cells demonstrated that in the highly heterochromatic chromosomes X and 9, G 2 -phase X-ray-induced chromosome damage persisted longer than in euchromatic chromosomes (Slijepcevic and Natarajan, 1994).…”
Section: Introductionmentioning
confidence: 96%
“…We have hypothesized that a deficiency in DNA repair in this region could account for the observed fragility. Some indirect evidence supports this working hypothesis: (1) there is a hierarchy in DNA repair, being the non-transcribed regions and the non-transcribed strand of active genes less efficiently repaired (Bohr et al, 1985;Mellon et al, 1986Mellon et al, , 1987Venema et al, 1990;Mullenders et al, 1991); (2) earlier studies demonstrated that highly repetitive heterochromatic alpha DNA from monkey cells was deficient in excision repair of chemical adducts, although damage induction was not (Zolan et al, 1982;Smith, 1987); (3) 1q12 is frequently broken in cells from Fanconi anaemia patients (Huret et al, 1988), an autosomal recessive genetic syndrome characterized by predisposition to leukemia and solid tumors, elevated spontaneous chromosome breakage, and inability to remove cross-linking lesions from DNA (reviewed by Strathdee et al, 1992); and (4) studies performed with Chinese hamster cells demonstrated that in the highly heterochromatic chromosomes X and 9, G 2 -phase X-ray-induced chromosome damage persisted longer than in euchromatic chromosomes (Slijepcevic and Natarajan, 1994).…”
Section: Introductionmentioning
confidence: 96%
“…Molecular cytogenetic investigations have also demonstrated that decondensation of the donor pericentromeric heterochromatic region and shortening of the recipient telomeric region contribute to the formation of an acquired JT [26]. The most frequent donor chromosomes in hematological disorders, particularly in myeloid lineage JTs, are chromosomes 1 and 3 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Only recently has a JT breakpoint (JTB) gene been located on human chromosome 1 at q21 which is known to be involved in various types of cancer [27].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been fewer than 70 JTs reported in hematological malignancies and solid tumors, in which unambiguous band designations have been assigned to both donor and recipient chromosomes [2]. To our knowledge, only 18 JT cases have been described in patients with a myeloid-lineage hematological disorder, 16 of which have been reported in patients with acute myeloid leukemia (AML), 1 with refractory anemia (RA) and 1 with an unspecified myeloproliferative neoplasm (MPN(u)) [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple translocations, in which an identical chromosome region is translocated to the telomeric region of a number of different chromosomes giving rise to several related cell lines, are a rare manifestation of chromosome abnormalities which have been termed "jumping translocations" (Shinohara and Nomura, 1988;Huret et al, 1989). We present a case of a 68-yearold male with ALL having a t(4;ll) clone with clonal evolution arising from two distinct jumping translocations of chromosome 1 and resulting in six variants.…”
Section: Introductionmentioning
confidence: 99%
“…We present a case of a 68-yearold male with ALL having a t(4;ll) clone with clonal evolution arising from two distinct jumping translocations of chromosome 1 and resulting in six variants. Features of five reported cases are reviewed Morris et al, 1984;Whang-Peng et al, 1984;Raimondi et al, 1987;Shinohara and Nomura, 1988;Huret et al, 1989). These show a predominance of B-lineage lymphoid malignancies.…”
Section: Introductionmentioning
confidence: 99%